Training in mitral valve surgery need not affect early outcomes and midterm survival: A multicentre analysis - Shi, W.; Hayward, P.; Yap, C.; Dinh, D.; Reid, Christopher; Shardey, G.; Smith, J. (2011)
Objective: Mitral valve surgery may be regarded as less favourable for training, due to greater mortality risk, technical complexity, and difficulty for the supervisor to observe. We examined this perception by reviewing a multicentre experience. Methods: We analysed a multicentre database over a 7-year period containing 2216 isolated and combined mitral procedures. Of these, 2048 were performed by consultants and 168 by trainees (92% vs 8%) of varying seniority. Preoperative characteristics, early postoperative outcomes and 6-year survival were compared between groups. Propensity-score matching was performed to correct for group differences. Results: Trainees were less likely to operate on patients, who had previously undergone coronary surgery (consultant 4.3% vs trainee 1.2%, p=0.043) and those with moderate to severe mitral regurgitation (86% vs 81%, p=0.012). There were no other statistically significant differences in preoperative variables, such as urgency, endocarditis and left-ventricular dysfunction. There were similar rates of mitral valve repair (48% vs 51%, p=0.48). Trainees were more likely to operate on rheumatic valve pathology (20% vs 28%, p=0.012). Intra-operatively, trainees had longer aortic cross-clamp times (119 ± 52 vs 136 ± 50. min, p=0.0001). At 30 days, mortality was comparable (4.5% vs 3.6%, p=0.56) with a trend towards higher any mortality/morbidity in consultant procedures (33% vs 26%, p=0.059). At 6 years, survival was similar (79 ± 1.4% vs 78 ± 4.0%, p=0.73). After derivation of 142 propensity-score-matched patient pairs, trainees cases still experienced longer cross-clamp times (121 ± 58 vs 137 ± 52. min, p=0.023), but there was similar 30-day mortality (4.2% vs 3.5%, p>0.99) and any mortality/morbidity (28% vs 24%, p=0.52). Six-year survival between matched pairs was also similar (74 ± 7.2% vs 80 ± 4.4%, p=0.64). Trainee status did not predict early or late adverse events after multivariate Cox regression with and without propensity-score adjustment. Conclusions: Trainee outcomes are not inferior even when corrected for risk. This suggests that excellent operative training and supervision can be achieved in mitral valve surgery. © 2011 European Association for Cardio-Thoracic Surgery.